2018
DOI: 10.1080/09593985.2018.1493759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in home high dose accelerometer-based feedback on perceived and actual use in participants chronic post-stroke

Abstract: In home high dose accelerometer-based feedback increased perceived paretic UE use and overall awareness of paretic UE use. Perception of use may serve as a first step to promote the behavioral change necessary to encourage actual paretic UE use, potentially decreasing the maladaptive effects of learned nonuse on participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…Previous studies have demonstrated that, in stroke patients, movement counts, as measured with accelerometers, are associated with the use of the affected arm-hand (Motor Activity Log score) [36, 37] and, at function level, with the Fugl-Meyer Assessment [38]. Next to quantifying paretic arm-hand use, accelerometers have also been used to provide feedback to further enhance the use of the affected hand in home-based situations [39]. Most studies consist of relatively small [27, 30, 40–44] and highly selected study populations [45] with short time intervals between baseline and follow-up measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that, in stroke patients, movement counts, as measured with accelerometers, are associated with the use of the affected arm-hand (Motor Activity Log score) [36, 37] and, at function level, with the Fugl-Meyer Assessment [38]. Next to quantifying paretic arm-hand use, accelerometers have also been used to provide feedback to further enhance the use of the affected hand in home-based situations [39]. Most studies consist of relatively small [27, 30, 40–44] and highly selected study populations [45] with short time intervals between baseline and follow-up measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The median ARAT scores for both groups showed an improvement during the four-week study intervention phase with the intervention group continuing to improve up to the eight-week follow-up outcome. The amount of use of the impaired arm as measured by the MAL and the accelerometers also indicated an increase for both groups, which continued up to the week eight out- 15 (10)(11)(12)(13)(14)(15)(16)(17)(18) 19 (16)(17)(18)(19) 19 (17)(18)(19)(20) 12 (10)(11)(12)(13)(14)(15)(16) 17 (12)(13)(14)(15)(16)(17)(18)(19) 15 (15)(16)(17)(18) ARAT: Action Research Arm Test; IQR: interquartile range; NIHSS: National Institutes of Health Stroke Scale. come for the intervention group but not for the control group.…”
Section: Resultsmentioning
confidence: 95%
“…15 Although participants reported that they thought they had used their impaired arm more, the accelerometer data did not show an actual increase in the amount of arm use. 15 In another study, 16 arm activity was measured by an actometer worn on the wrist which prompted arm movement with a vibration cue every five minutes over a three-hour period. This study found that the sensory cueing led to more arm movements for the intervention group, but there was no impact upon functional performance.…”
Section: Introductionmentioning
confidence: 86%
“…While not labeled as EMI, a few studies have used mHealth technologies to deliver feedback about movement behavior or physical activity levels outside clinical settings. [60][61][62][63][64] The provision of quantitative feedback from activity monitors can include objective measures of activity (e.g. movement or step count, time spent in moderate intensity activity), graphs of daily activity, or encouragement of activity goals (e.g.…”
Section: Ecological Momentary Intervention For Behavior Change In Strmentioning
confidence: 99%
“…Another study investigated the impact of delivering feedback collected through wrist-worn activity monitors on perceived and actual paretic arm use. 62 During a 3-week period, feedback was provided during seven follow-up sessions and consisted of discussions and graphs about the amount of use of the paretic arm.…”
Section: Ecological Momentary Intervention For Behavior Change In Strmentioning
confidence: 99%